ESTIMATION OF LOSSES DUE TO PULSE BEETLE IN CHICKPEA - N. R. JAT,; B. S. RANA,; S. K. JAT, (The Bioscan, 2012)
The losses caused by pulse beetle were estimated by releasing 1, 2, 4, 8 and 16 pairs of adults in jars each containing 500g chickpea grains. The lowest mean grain damage, weight loss and germination loss were recorded in case of 1 pair of adult pulse beetle i.e., 7.79, 1.81 and 4.55 per cent. While, highest losses were recorded in case of release of 16 pair i.e., 60.93, 13.99 and 44.57 per cent after 30 days of storage, respectively. The losses followed the same trend after 90 days of storage and reached to highest i.e., 41.44, 19.26 and 29.27 per cent in case of release of 1 pair of adult, While, 100, 46.13 and 100 per cent, respectively, in case of release of 16 pair of adult pulse beetle. The losses were increased with increase in storage period.